Implementasi Kebijakan Fiskal dan Moneter Syariah terhadap Stabilitas Ekonomi - Ahmad Wahyudi Zein; Ismaika Hayati Hasnah; Asyami Ramadhani; Free May Santri (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
Economic stability is a primary objective in the management of a country’s economy, as it directly affects economic growth, public welfare, and sustainable development. In conventional economic practice, dependence on interest-based instruments and speculative activities often triggers economic instability, such as high inflation, financial crises, and unequal income distribution. These conditions have encouraged the development of Islamic economics as an alternative economic system grounded in Sharia principles. This study aims to analyze the implementation of Islamic fiscal and monetary policies and their role in maintaining economic stability. This research employs a qualitative method with a literature review approach, drawing on various scholarly sources, including national and international journals, Islamic economics reference books, and relevant policy documents. The findings indicate that Islamic fiscal policy, through instruments such as zakat, infaq, waqf, and public asset management, plays a significant role in income redistribution and the reduction of economic inequality. Meanwhile, Islamic monetary policy, which rejects the use of interest and emphasizes profit-and-loss sharing mechanisms, contributes to strengthening the real sector and reducing speculative practices in the financial system. The integrated implementation of Islamic fiscal and monetary policies is proven to contribute to long-term economic stability by creating a balance between economic growth and social justice. Therefore, the application of Sharia-based macroeconomic policies can serve as a strategic alternative in addressing modern economic challenges and in realizing a more stable, inclusive, and sustainable economic system.